Floral capitula and essential oil production analysis of chamomile (Chamomilla recutita) cultivars at different times of harvest - Matsushita, Milton S.; Deschamps, Cícero; Corrêa Júnior, Cirino; Machado, Marília P. (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Chamomile [Chamomilla recutita (L.) Rauschert] belongs to the Asteraceae family and is part of a large medicinal plant group that is cultivated and used in Brazil and in the world. The objective of this study was to evaluate the floral capitula productivity and essential oil content and composition of four cultivars of chamomile in three harvesting periods. The experiment was conducted at the Canguiri Experimental Station (UFPR) from May 15th to September 9th, 2015. Four cultivars of chamomile were evaluated, from commercial products purchased in different countries: Twinings (England), Auchan (Spain), Lipton (Scotland) and Mandirituba (Brazil), which is traditionally grown in Paraná. The experiment design used randomized blocks in a 4×3 factorial scheme (4 cultivars and 3 harvesting periods), with four replicates. At 96 days after planting, manual harvests were performed, for a total of three harvests. After each harvest, the floral chapters were dried. The extraction of the essential oil and the identification of the chemical constituents of the essential oil were carried out in the Laboratory of Ecophysiology of UFPR. The harvest time affected the productivity of the floral capitula and essential oil, being higher in the first (276.9 and 0.71 kg ha-1, respectively) and third harvests (262.6 and 0.77 kg ha-1, respectively). The cultivars and harvests did not influence the essential oil percentage (0.22 to 0.29%) obtained from the floral capitula; however, they contributed to the definition of the produced chemical compound.